Efficacy of BCG vaccination against COVID-19 in health care workers and non-health care workers: A meta-analysis of randomized controlled trials - Zhuoyang Xia; Jiahao Meng; Xuanyu Wang; Pan Liu; Yumei Wu; Yilin Xiong; Baimei He; Shuguang Gao (PLoS ONE, 2025)
Background The Bacillus Calmette-Guérin (BCG) vaccine has shown potential non-specific protection against infectious diseases through “trained immunity”, which may offer cross-protection against viral infections. However, there is no consensus on whether BCG vaccination could prevent COVID-19 or reduce its symptoms. Methods PubMed, Cochrane Library, Embase and Web of Science were searched for randomized controlled trials on BCG vaccination and COVID-19 prevention, covering studies from the inception of each database to 2 May 2024. We included studies where participants, not infected with COVID-19, were vaccinated with BCG or placebo. We excluded non-randomized trials, studies without full texts, unrelated interventions, and those not reporting relevant outcomes. Clinical data on COVID-19 infection, severity, hospitalization, mortality, and other adverse events, were extracted and analyzed. The DerSimonian–Laird random-effects model and the Cochrane Collaboration’s risk of Bias Tool were used for analysis and risk of bias assessment. Results A total of 12 RCTs involving 18,086 patients were finally included. For the prophylactic effect of BCG on COVID-19, pooled results showed no statistically significant difference between BCG and placebo (pooled RR 1.02; 95%CI: 0.91–1.14). There was no statistically significant difference between non-health care workers (pooled RR 0.91; 95%CI: 0.67–1.24) and health care workers (pooled RR 1.03; 95%CI: 0.93–1.15). Regarding COVID-19 severity, no significant difference were found for asymptomatic (pooled RR 1.18; 95%CI: 0.81–1.72), mild to moderate (pooled RR 0.99; 95%CI: 0.84–1.17), severe COVID-19 (pooled RR 1.25; 95%CI: 0.92–1.70), hospitalization (pooled RR 0.93; 95%CI: 0.58–1.50) or all-cause mortality (pooled RR 0.60; 95%CI: 0.18–1.95) between BCG and placebo groups. Subgroup analysis also showed no significant difference between BCG and placebo in non-health care workers or health care workers. Conclusions Vaccination of BCG could not effectively prevent COVID-19 infection or decrease COVID-19 symptoms both in non-health care workers and health care workers.